Agronomic performance of maize (Zea mays L.) breeding lines derived from a low nitrogen maize population - Kamara, A.Y.; Kling, J.G.; Menkir, A.; Ibikunle, O. (Cambridge University Press, 2003)
Eighteen S1 lines of maize (Zea mays L.) derived from a low nitrogen tolerant pool and two inbred lines were evaluated for agronomic performance under moderate N conditions in the southern Guinea savannah of Nigeria. Generally, the breeding lines differed in yield, growth, vertical rootpulling resistance, N-uptake and N-use efficiency. Breeding lines with high vertical root-pulling resistance took up more N and utilized it more efficiently. They also showed better agronomic performance and recorded higher yields. Principal component and cluster analyses classified the breeding lines into six groups. The results of principal components analyses (PCA) suggest that the most important variables for the classification of the S1 lines were grain yield, plant height, total dry matter during the grain-filling period and at maturity, N-accumulation, N-uptake and N-use efficiency. Other important traits were days to silking, anthesis-silking interval, ears per plant, harvest index and vertical root-pulling resistance. Two groups containing a total of 14 S1 lines that had higher agronomic performance than others are recommended for further evaluation under severe N stress to ascertain their tolerance of low N stress before recombination to form a new population for the next cycle of selection.